Determinantes do investimento estrangeiro direto no Brasil no período de 1987-2004 - Santos Filho, Manoel Miguel dos (2006)
the long one of the last years, more necessarily from the decade of 1990, the Brazilian economy suffered deep economic, decurrent transformations of occurred movements of financial liberalization in the main world-wide markets. Ahead of this liberalization, the financial markets had lost its borders, facilitating the investments in the most diverse countries of the world. Brazil, perceiving the new reality, gradual opened its borders in the beginning of the decade of 1990 to the foreign capital, reason for which the economy, from now on, absorbed, as one of the transformations most visible, raised volumes of ingression of foreign investments right-handers. In this direction, the central objective of this study is esteem, on the basis of given of secular series, main determinative of the flows of IED for Brazil, considering the period of 1987 the 2004. The gotten results of the study had pointed that traditional factors as, the implantation of the Real Plan, level of commercial opening and real tax of interests, are main determinative of the foreign investments the right-handers for Brazil. 0 variable as index of the stock exchange of São Paulo, tax of inflation and growth of the American GIP also exert influence on the ingression of IED in Brazil.